NLRX1 dampens oxidative stress and apoptosis in tissue injury via control of mitochondrial activity - Stokman, Geurt; Kors, Lotte; Bakker, Pieter J; Rampanelli, Elena; Claessen, Nike; Teske, Gwendoline J D; Butter, Loes; van Andel, Harmen; van den Bergh Weerman, Marius A; Larsen, Per W B; Dessing, Mark C; Zuurbier, Coert J; et al. (The Journal of experimental medicine, 2017)
Mitochondrial dysfunction is the most prominent source of oxidative stress in acute and chronic kidney disease. NLRX1 is a receptor of the innate immune system that is ubiquitously expressed and localized in mitochondria. We investigated whether NLRX1 may act at the interface of metabolism and innate immunity in a model of oxidative stress. Using a chimeric mouse model for renal ischemia-reperfusion injury, we found that NLRX1 protects against mortality, mitochondrial damage, and epithelial cell apoptosis in an oxidative stress-dependent fashion. We found that NLRX1 regulates oxidative phosphorylation and cell integrity, whereas loss of NLRX1 results in increased oxygen consumption, oxidative stress, and subsequently apoptosis in epithelial cells during ischemia-reperfusion injury. In line, we found that NLRX1 expression in human kidneys decreased during acute renal ischemic injury and acute cellular rejection. Although first implicated in immune regulation, we propose that NLRX1 function extends to the control of mitochondrial activity and prevention of oxidative stress and apoptosis in tissue injury.